(untitled) (The Review of Diabetic Studies, 2024)
Background: The emergency department (ED) plays a vital role in providing life-saving services in hospitals worldwide. province, Saudi Arabia, the Ministry of Health introduced the “Door to Disposition” key performance indicator (KPI) to enhance ED service quality by addressing overcrowding, limited bed capacity, delays in patient transfer, and complex logistical inefficiencies. Emergency Medical Services (EMS) are undergoing a rapid transformation in Saudi Arabia under the national Vision 2030 framework, which seeks to enhance healthcare quality, accessibility, and responsiveness. Paramedics have emerged as key agents in achieving these goals through the delivery of advanced pre hospital care, technological integration, and patient-centered service models. The review concludes by proposing a strategic framework that aligns workforce development and technological advancement with Vision 2030 objectives for sustainable, high-quality emergency healthcare of teamwork in nursing. The aim of this systematic review: To assess the effecting between emergency department Overcrowding and Outcomes of teamwork care in Saudi Arabia 2024. Methods: This systematic review was conducted based on the Preferred Reporting Items for Systematic Reviews (PRISR) 2024 review protocol. We systematically reviewed the emergency department Overcrowding and Outcomes of teamwork care. Results: particularly due to their constant patient interaction regarding effecting between Emergency Department Overcrowding and Outcomes of nursing care on patient: A Systematic Review at Saudi Arabia 2024. Prolonged Overcrowding and Outcomes of care and consultation time, and physical response to the final decision, and leads to burnout nurses and staff, wrong diagnoses, and management plans. Crowding issues are resolved by awareness, triad systems, and technological and telemedicine services. Conclusion: ED crowding is becoming a major problem in the delivery of holistic care services in Saudi Arabia. Although significant improvements have been made, workforce shortages and overcrowding in emergency departments continue to be major challenges. Emergency departments in major cities often experience overcrowding, which results in longer wait times and overburdened healthcare professionals.